Polska spółdzielnia energetyczna w świetle dyrektywy Parlamentu Europejskiego i Rady Unii Europejskiej 2018/2001 z dnia 11 grudnia 2018 roku w sprawie promowania stosowania energii ze źródeł odnawialnych - Kupiec, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Citizen energy is a key element of the energy and climate policy of the European Union. EU regulations create a legal framework for the functioning of associations managed by citizens to develop RES projects. The Polish legislator has regulated the concept of an energy cooperative in order to activate citizens in the field of energy. This article compares the legal regulation of the energy cooperative with the content of Directive 2018/2001 of the European Parliament and of the Council of the European Union of 11 December 2018 on the promotion of the use of energy from renewable sources. The aim of the article is to demonstrate that the concept ofan energy cooperative does not correspond to the content of the above-mentioned EU Directive. The article proposes appropriate amendments to the energy cooperative.
Keywords: energy cooperative; RES; energy community; civic energy